Why do Voters Allow a Tax Levy for Library Management? - Suzuki, Issei; Koizumi , Masanori (Bobcatsss, 2023)
From the late 20th century, economic pressure on public library budgets rises as government funding has declined (Aabø, 2009; Child & Goulding, 2012). Under increasing financial pressure, creating a procedure for how public libraries can provide fulfilling services to residents is one of the essential issues in public library management. As a result, internationally, management models of public libraries have become more diverse in terms of dealing with financial problems. For example, there are management models such as the Designated Manager System (privatisation of public libraries) in Japan, the Community Libraries (managed by volunteers) in England, and the Combined Libraries (hybridisation of different types) in the Nordic Countries. All of these management models are a means to address the financial challenges of public libraries. In the same way in the United States, library districts are receiving much attention as a management model that responds to financial deterioration. Library districts are Special-Purpose Governments that have a tax levy and bond authority for library management. Also, library districts are formed through a referendum. Recent studies have demonstrated that library districts' revenues are more stable over the long term than those of other legal bases, such as General-Purpose Governments and Non-Profit Organisations (NPOs) in the United States (Elliott, 2013; Goldman, 2018). However, forming library districts are not simple, because it means a tax increase for residents. Nevertheless, the number of library districts has increased since the late 20th century. Why do voters allow a tax levy for library management? In this paper, we examined in detail the arguments regarding the formation of library districts through an in-depth case analysis. In this research, we analysed the “voters’ pamphlet” distributed to residents at the time of referendum for forming the Josephine Community library district in the state of Oregon. The “voters’ pamphlet” described detailed opinions of residents regarding formation of library districts. In the analysis, based on the constituents of library district management presented through a comprehensive literature review by Suzuki and Koizumi (2020), we analysed the opinions of the residents through a qualitative content analysis. Specifically, through the analysis of opinions in favour, we illustrated the factors that residents allow to form library districts. Second, through the analysis of opinions in opposition, we illustrated the factors that residents opposed to form library districts. As a result, we showed the following research results. Those in favour emphasised the significance of public libraries in the community. On top of that, they allowed the formation of the library district as a means to provide library services sustainably. In particular, they were satisfied with the current library service and hoped to enhance it further. On the other hand, many opponents opposed the formation of the library district, even though they recognised the value of public libraries. It was against the permanent taxation of the library district. Also, opponents called for donations to public libraries. In other words, the significance of public libraries in the community was a common understanding among residents. The argument is how much the residents are willing to accept the burden of providing library services.